Pengaruh Gaya Kepemimpinan dan Komunikasi melalui Fasilitas Kerja terhadap Kinerja Karyawan PT. Suryagita Sarana Jaya - Rudy Pudjut Harianto; Muhammad Oceano Fauzan (J-MAS (Jurnal Manajemen dan Sains), 2023)
In this study the variables used were leadership style, communication, work facilities and performance of employees at PT Suryagita Sarana Jaya. The purpose of this research is to provide input to PT Suryagita Sarana Jaya and add knowledge to readers. The research method used is by distributing questionnaires to employees of PT Suryagita Sarana Jaya, in answering the questionnaire the respondents simply mark the column that contains the Likert's Scale (1 – 5) leadership style on work facilities has a positive and significant effect, while work communication has a negative and insignificant effect on work facilities and work facilities have a positive and significant effect, so does the variable leadership style on performance has a positive and significant influence, while communication has a negative and insignificant effect on performance While simultaneously leadership style, communication through work facilities has an influence and significant.